Desenvolvimento de um algoritmo híbrido utilizando metaheurísticas aplicado a uma plataforma Internet Protocol Television – IPTV - Weissheimer Júnior, Carlos Alfredo (Universidade do Vale do Rio dos Sinos, 2012)
The Internet Protocol Television Technology (IPTV) is an impacting factor on society. It has been exploited by different means of transmission to the delivery of multimedia content over service based on Internet Protocol (IP). Currently, IPTV is the subject of several studies, since it can bring many benefits to society, such as interactivity support and increased interoperability with home networks. This paper presents the development and implementation of a computational model based on the application of metaheuristics on an IPTV platform in order to develop a hybrid algorithm using the metaheuristics Tabu Search (TS) and Genetic Algorithm (GA). This algorithm makes it possible to analysis and study of the following parameters: baud rate, audio quality, number of customers and network bandwidth in order to find the best setting for the IPTV transmission given the client characteristics. After validating the algorithm, experiments are performed to help understand the dynamics of the system and enable a good solution that can be simulated in the Network Simulator 3 (NS3).
Keywords: Genetic algorithm; Search; Metaheuristics; IPTV; Algoritmos genéticos; Tabu; Busca; Metaheurísticas; ACCNPQ::Ciências Exatas e da Terra::Ciência da Computação